Effects Of Feeding Cow Urine Ark And Aloe Vera Extract On Haematological Study In White Leghorn Chicken. - Panicker, Anjana; Sharma, R.K.; Trivedi, Mahesh S.; Jain , Nitesh Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was carried out to find the effect of administration of Cow urine ark and Aloe Vera extract on haematological parameters in White leghorn chicken. A significant increase was observed in Hb, TEC, TLC and PCV after administration of cow urine ark and Aloe Vera extract. The study reveals that the cow urine ark and Aloe Vera stimulates process of haematopoiesis.
Keywords: Aloe Vera; Cow Urine Ark; Haematological; White Leghorn Chicken